MAKNA DAN IDENTITAS BUDAYA BAJAWA NUSA TENGGARA TIMUR DALAM FILM SAHABAT KECIL EPISODE 2 - Apolonius Kristoforus Ga’a; Fathul Qorib; M Abd Ghofur (Universitas Tribhuwana Tungga Dewi, 2022)
The film “Childhood Friend episode 2” is a film telling the story about the love of a couple who had to run aground because of the differences in social caste between the two families. The reason for choosing the film